STUDY OF THE QUANTITY OF PHENOLIC COMPOUNDS AND BIOELEMENTS IN THE COMPOSITION OF TARAXACUM OFFICINALE WIGG. S.L., GROWING IN THE TERRITORY OF FERGANA (Scientific journal of the Fergana State University, 2025)
For the first time, using the HPLC method and instrumental neutron activation analysis, the quantitative composition of 6 flavonoids and 38 macro- and microelements in the above-ground parts of Taraxacum officinale Wigg. s.L., growing in the territory of Fergana, was studied. It was established that dihydroquercetin (25.2 mg/g) predominates in the composition of Taraxacum officinale Wigg. s.L., along with macro- and microelements such as Na (920 mg/kg), Ca (38700 mg/kg), Fe (2970 mg/kg), Mn (94.5 mg/kg), and Cu (15 mg/kg). The amount of toxic elements in the plant does not exceed the maximum permissible concentration.